Evaluating the effectiveness of conservation priorities in mitigating agricultural threats to China’s vertebrates - Can Yang; Geli Zhang; Xi Zhang; Yuzhe Li; Zhichao Li; Qinghao Wang; Jinwei Dong (Ecological Indicators)
Conservation priorities (CPs), considered at least 44 % of the terrestrial area globally, would be a critical tool for avoiding a dramatic collapse of biodiversity. Agriculture is widely recognized as the largest driver of biodiversity loss. However, in China, where the demand for food production and croplands is the highest, the threats posed by agricultural activities to endangered vertebrates–particularly across different taxonomic classes–have not been thoroughly assessed. Additionally, the effectiveness of CPs in addressing these threats needs quantification across the country. In this study, we utilized high-resolution cropland data and information on threatened vertebrates to analyze the threats posed by croplands, while also evaluating the effectiveness of CPs in China. Our findings indicate that croplands in the Middle-Lower Yangtze Plain and Northeast China represent the most significant threats to threatened birds, with 1,346 and 751 identified risk spots, respectively. Furthermore, croplands in Southwest China pose considerable threats to threatened mammals and amphibians, with 851 and 469 risk spots, respectively. Importantly, many of these risk spots are not covered by CPs, revealing a significant gap of 1.2 × 105 km2, primarily in the Middle-Lower Yangtze Plain (3.6 × 105 km2) and Southwest China (3.5 × 105 km2). These findings provide critical insights that can inform strategies aimed at achieving the goals of the Kunming-Montreal Framework in China.